Deer run home : a novel in verse - LeZotte, Ann Clare (Scholastic, Inc., 2024)
With a family who refuses to learn sign language, twelve-year-old Effie is mostly cut off from human communication at home, unable to speak of her abusive stepfather or violent father--only her interpreter understands, and Miss Kathy is willing to take Effie's case to court to provide her with a safe home. Told in verse.